PROTEKSI DINI PENYAKIT KORUPSI BERBASIS SYARIAH - Abdurrahman, Abdurrahman (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
AbstractCorruption, collusion and nepotism in our nation has become an integral part. They can not be separated, so it is still very difficult to be erased. Resistance to corruption that has pushed by a number of people, yet seem to produce something significantly. Efforts to eradicate corruption is our task. Although this certainly is a very difficult choice, because it is more based on the bitter fact that the corrupt behavior has dominated in all aspects of life. There are a myriad of empirical fact which has been pointed out that there is no empty space in this country that are not filled by the corruptor. However, it does not mean that the problem of corruption in this country can not eradicate. Eradication of corruption must be done at every layer of society that no longer corrupt culture upon all parties. This article is focused on the approach to the implementation of Islamic law in order to solve all the problems we are facing together, as children of the nation, in terms of combating corruption.Kata-kata kuncikorupsi, implikasi korupsi, upaya pencegahan, syariat islam